The kit for identification of antibodies against Lassa and Ebola viruses by indirect immunofluorescence - L. M. Rustamova; S. F. Semenov; N. L. Bogdanova; A. S. Vladyko; A. G. Krasko (Биопрепараты: Профилактика, диагностика, лечение)
Timely diagnosis of particularly dangerous infections caused by viruses Ebola and Lassa is crucial in organization of anti-epidemic measures in the case of important of the disease on the territory of the Republic of Belarus. The main method of rapid response at revealing hemorrhagic fevers Lassa and Ebola still is the method of indirect immunofluorescence. In this work the elaboration of the kit for detection of antibodies to exciters of extremely dangerous viral infection Lassa and Ebola by indirect immunofluorescence method is described.